Synthesis and optical properties of light-emitting polyfluorene derivatives - Philaiwan Aiamsen (2018)
The emitting-polymers, Polyfluorene (PF) and Poly(fluorene- benzothiadiazole-quinoline) [PF-BT-QL], have been synthesized by the Suzuki coupling reactions. The properties of polymers were characterized using UV-Vis spectroscopy, GPC, DSC, TGA, Photoluminescence (PL), Fluoresence (FL), Electroluminescence (EL) spectroscopy. The synthetic polymers were soluble in common organic solvents and easily spin-coated onto the indium-tin oxide (ITO)-coated glass substrates. Light-emitting devices (LEDs) with ITO/PEDOT:PSS/polymer/LiF/Al configuration were fabricated, and the devices using copolymers showed red shift EL spectra relative to that of PF. The turns on voltages of copolymers were lower than that of PF. Copyright © Taylor & Francis Group, LLC.